Legislasi Hukum (Parliament Made Law) dengan Pendekatan Fiqh - Nawawi Nawawi (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2017)
Law made by parliament is not value-free or neutral, because of political configuration in that process. Dominant party that has the power of authority becomes the winner in trade-offs of various concerns. At the result of that product made by parliament does not reflect the real case and the public concerns. If the political configuration tends to be authoritarian, it will generate a conservative law and orthodox law, but if the political configuration tends to be democratic, it will generate a responsive law and autonomous law. In order to accommodate all the public behavior and fair society, it should meet at least three criteria. First, limitative in very detailed which there is no interpretation in authorities profitable. Second, participatory in the process of establishment contains the aspirations and interests of the grass root. Third, aspirational-democratic in the legal materials accomodate the aspirations of the people in order to apply democracy. The function of the law as a political tool can be understood that the system of law in Indonesia, acts is a product of the Indonesian Legislative Assembly and Indonesian government so that very difficult to separate between law and politics. It is directly related to the state.